Behind Organizational Change: Employee Stories of Challenges and Performance - Muslikhun, Muslikhun (LPPPIPublishing, 2025)
This study aims to understand employees' experiences in dealing with organizational change and its impact on work performance at PT XYZ using a phenomenological approach. Organizational changes that include restructuring and digitalization of work processes have led to various emotional and behavioral reactions from employees. Data were collected through in-depth interviews with a number of employees who experienced the change process firsthand. Data analysis used Colaizzi's phenomenological technique to uncover the deep meaning of the employees' experiences. The results showed that employees initially experienced uncertainty and anxiety that affected their motivation and work performance. The adaptation process took place through learning and adjusting work patterns that were strongly influenced by open communication and managerial support. Some employees interpreted the changes as opportunities for self-development and performance improvement. This research confirms that the success of adaptation and performance is highly dependent on how employees interpret change and the important role of management in supporting the process. The findings provide valuable insights for organizations in designing humanistic and effective change management strategies to improve employee well-being and productivity.